Assessing the potential of bone marrow concentrate for cartilage repair and regeneration in animal models : a systemic review - Nabillah Abd Radzak,; Malliga Raman Murali,; Tunku Kamarul, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Bone marrow concentrate (BMC) has been emerging as a promising regenerative source to accelerate cartilage regeneration in cartilage injuries and osteoarthritis. Though the number of stem cells in BMC is limited, BMC is rich in growth factors that promote stem cell differentiation and tissue regeneration. Despite of multiple reports available on the use of BMC for cartilage repair in humans and its use in clinical settings, only limited number of pre-clinical proof of concept studies have been reported in animal models. Hence, a systematic review focusing on the potential of BMC for the treatment of cartilage defect in animal models has been conducted. The systematic search of literature using three popular databases, ISI Web of Knowledge, PubMed and Scopus, were conducted without year restriction. Fifteen (n = 15) studies were found appropriate and included in this review. All of the included studies were of different animal models with cartilage defect. 13 out of 15 studies reported that the usage of BMC gave the best outcome compared to other treatment methods. Most of the findings provided good scoring on the tissue repair and the histological outcome. However, most of the BMC group outcomes did not give a significant difference when compared with other interventions such as the addition of platelet rich plasma, erythropoietin, hyaluronic acid, transforming growth factor, autologous tissue implant, genetic modification or scaffoldings. In conclusion, the published studies do suggest that BMC could provide a better cartilage repair. However, more preclinical studies are required to provide definitive conclusions.